Social Transformation and PMII Cadreization in Addressing Youth Moral Crisis - Misbahul Arifin (PT Riset Mandiri Nusantara, 2025)
This study focuses on the social transformation carried out by the Indonesian Moslem Student Movement (PMII) in addressing the moral crisis among young generations, which is marked by the weakening of integrity, low social awareness, and the rise of pragmatic behavior that threatens the socio-humanitarian order. The purpose of this research is to analyze how PMII’s cadre system serves as a strategic instrument in shaping moral awareness, building character, and strengthening the social capacity of youth amidst the dynamics of social change. The method employed is library research by analyzing academic literature, scholarly articles, books, and organizational documents, with a descriptive-analytical approach used to identify the correlation between the moral crisis of young people and PMII’s cadre system as a solution for social transformation. The findings reveal that PMII’s cadre system provides an effective response to the moral crisis by internalizing religious, intellectual, and humanitarian values, thereby producing cadres who are not only organizationally militant but also act as agents of change with strong social orientations. The implication of this study emphasizes that youth organizations grounded in Islamic values have significant potential in shaping a generation with character, integrity, and social transformative capacity, while also highlighting the importance of integrating formal education, non-formal learning, and youth organizations in responding to moral and social challenges in the era of globalization.